Epigenetics in Odontogenesis and its Influences - Li, Chuwen; Cui, Yujia; Zhou, Changchun; Sun, Jianxun; Zhou, Xuedong (Current Stem Cell Research & Therapy, 2018)
Background: Odontogenesis is fundamentally controlled by the genome. However, epigenetic factors have indispensable effects during odontogenesis. Previous studies have shown that exogenous factors, such as the environment, that cause hypomethylation and hypermethylation in DNA may lead to dental differences in monozygotic twin pairs. In addition, abnormalities in epigenetic regulation could induce disruptions in odontogenesis, thereby causing tooth malformation or agenesis. Objective: This review overviews the epigenetic mechanisms involved in odontogenesis with the aim of establishing a fundamental vision of tooth development, which might be useful in further research in odontogenesis and therapy for dental diseases. Results: We summarized articles about epigenetics in odontogenesis. Here, we present concrete epigenetic regulation mechanisms in odontogenesis that have been reported previously, following the order of microRNA, DNA methylation and histone modification. Conclusion: Epigenetic factors influence the proliferation, differentiation or apoptosis of cells that play indispensable roles during the process of odontogenesis which have the ability to exquisitely regulate the tooth number, size and shape.
Keywords: histone modification